Contilistat, a New Multitarget Small Polyfunctionalized Indole Derivative - Toledano-Pinedo, Mireia; Diez-Iriepa, Daniel; Porro-Pérez, Alicia; Schäker-Hübner, Linda; Hanl, Maria; Samadi, Abdelouahid; Almendros, Pedro; Iriepa, Isabel; Rodríguez-Fernández, M. Mercedes; Griñán-Ferré, Christian; Siwek, Agata; Wolak, Małgorzata; Satała, Grzegorz; Bojarski, Andrzej J.; Doroż-Płonka, Agata; Handzlik, Jadwiga; Godyń, Justyna; Knez, Damijan; Gobec, Stanislav; Więckowska, Anna; Hansen, Finn K.; Marco-Contelles, José (Synlett, 2024)
We describe the design, synthesis, and in vitro biological evaluation of contilistat, a novel polyfunctionalized indole derivative designed as a hybrid of contilisant and vorinostat containing key pharmacophoric groups of both parent ligands.
Keywords: docking analysis; medicinal chemistry; multitarget drugs; indoles; contilistat